POLA KONSUMSI SUMBER PURIN, AKTIVITAS FISIK DAN STATUS GIZI DENGAN KADAR ASAM URAT PADA LANSIA DI PUSKESMAS KECAMATAN MAKASAR JAKARTA - Gina Ganda Fitriana; Adhila Fayasari (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Degenerative processes can decrease the endurance in elderly that leads to health problem such as gout. Gout is a metabolic disorder, which is indicated by an increase uric acid in bloodstream (hyperuricemia). Factors affecting high level of uric acid are purine intake, physical activity and nutritional status. The aim of this study was to analyze the relationship between consumption pattern of purine source food, nutritional status and physical activity with uric acid level in elderly. The study design was cross sectional. The sample consisted of 100 subyekts at Puskesmas Kecamatan Makasar. The analytical used chi square. Patterns of food consumption of purine sources were measured using FFQ questionnaires which was then cut off into into 2 categories: low-moderate purine category with score <55 and high purine category with a score of ≥55 physical activity and nutritional status were measured using questionnaires, uric acid levels was obtained by looking at laboratory results or from patients' medical records. There was 10% of subyekts withlo- moderate uric acid levels and 90% of subyekts with high purine consumption pattern. Based on the results of chi square test there was a significant difference (p <0.05) between the consumption pattern of purine source food with normal uric acid and high uric acid. There was a relationship between consumption pattern of purine food source with uric acid level in elderly.